Stent Thrombosis Patients with Hyporesponsiveness to Clopidogrel, Prasugrel, and Ticagrelor: A Case Series Using Short Thromboelastography - Bartosz Olechowski; Alexander Ashby; Nalyaka Sambu; Michael Mahmoudi; Nick Curzen (Case Reports in Medicine)
Patients after percutaneous coronary intervention (PCI) with stent implantation and functional hyporesponsiveness to P2Y12 inhibitors are at higher risk of ischaemic events, particularly stent thrombosis (ST). It is currently not routine practice to assess the functional response to these agents. However, concern over functional hyporesponsiveness to clopidogrel has led to widespread uptake of prasugrel and ticagrelor as the default P2Y12 inhibitor after stent implantation in patients with acute coronary syndrome. Here we report, for the first time, 3 cases in which patients who have had ST exhibit hyporesponsiveness to clopidogrel, prasugrel, and ticagrelor.